2008
DOI: 10.5194/nhess-8-745-2008
|View full text |Cite
|
Sign up to set email alerts
|

Association of the negative anomalies of the quasistatic electric field in atmosphere with Kamchatka seismicity

Abstract: Abstract.One hundred three cases of a bay-like depression in the strength of the Ez component of the quasistatic electric field in the near-Earth atmosphere, observed from 1997 to 2002 on Kamchatka, have been analyzed statistically. It has been shown that the most probable length of a bay is 40-60 min. The most probable drops in Ez are minus 106-300 V/m. The dependence of these values on an earthquake class and a distance to the epicenter was not found. The probability of earthquake prediction over 24 h before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 4 publications
3
32
1
Order By: Relevance
“…Various reports of atmospheric electrical field anomalies can be found in the literature (e.g., Kachakhize et al, 2009;Smirnov, 2008), although no clear conclusions have been drawn at this time. Thus, we believe that in the near future, a deeper inspection of AE variations is required because these studies could be critical for obtaining a better comprehension of seismo-electromagnetic phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Various reports of atmospheric electrical field anomalies can be found in the literature (e.g., Kachakhize et al, 2009;Smirnov, 2008), although no clear conclusions have been drawn at this time. Thus, we believe that in the near future, a deeper inspection of AE variations is required because these studies could be critical for obtaining a better comprehension of seismo-electromagnetic phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…There has yet to be performed a statistical analysis taking into account a larger number of earthquakes. Recent measurements and analyses of variations of the vertical electric field connected to earthquakes (and also simultaneously of other parameters characterizing the electrical activity in the point of observation) are described in (Mikhailov et al, 2004;Smirnov, 2005;Mikhailov et al, 2005). The observations showed that the anomalies of the daily changes of the quasi-stationary vertical electric field in the atmosphere near the Earth's surface before earthquakes have the form of spikes.…”
Section: Local Pulses Of the Atmospheric Electric Field -A Possible Rmentioning
confidence: 99%
“…In particular, the modification of so called "Frenkel's model" (Liperovsky et al, 2008) of the atmospheric capacitor (based on radon emission), in opinion of the authors, may be effective only for the Far East region and partially for the Middle Asia region. Though, according to the works of Mikhailov et al (2004) and Smirnov (2005Smirnov ( , 2008, the mechanism of electric conduction variation of the atmosphere is vague even for the Kamchatka region where volcanic earthquakes are especially frequent and the emanation effect of radon is much more probable here than in regions with geological structures different from the Far East, e.g., the Caucasus. Consequently, it is logical to assume that (except special cases) the change of vertical electric current intensity in the atmosphere is chiefly connected with the change of electric field stress.…”
Section: Introductionmentioning
confidence: 99%